Workload Related Stress and Job Effectiveness of University Lecturers in Cross River and Akwa Ibom States, Nigeria - Usoro, Abosede A.; Etuk, Grace R. (Asian Journal of Social Sciences and Management Studies, 2016)
The strength of any organization largely depends on her workforce but work load related stress can affect the effectiveness of such organizational workforce. As an apex institution of knowledge, the Nigerian university system has a lot to contribute towards the nation’s manpower development, however studies have shown that there is a high level of workload related stress among university lecturers in Nigeria. Against this backdrop therefore, this study was articulated to determine the extent to which such work load related stress influences job effectiveness among university lecturers in Akwa Ibom and Cross River States, Nigeria. The Job demand control theory of Karasek and Theorell (1990) provided the theoretical framework for the study, while the cross sectional survey research was deployed as the study design. Samples were drawn from the two Federal Government owned universities in the states under study, namely: University of Uyo and University of Calabar. Data were obtained through structured six (6) point Likert scale questionnaires, while the one-way analysis of variance (ANOVA) was utilized to test the study hypothesis. The results showed that, workload related stress significantly influence the job effectiveness of lecturers in terms of publication, community service and teaching effectiveness. Appropriate recommendations are also made for improvement.